The Impact of Corporate Governance on Earnings Management of Portuguese Listed Firms - Lisboa, Inês (2021)
This work aims to analyze the impact of corporate governance characteristics on earnings management of Portuguese non-financial listed firms, for the period 2012–2016. Using panel data, we regress discretionary accruals, a proxy of earnings management, against corporate governance characteristics and control variables. The main results show that only two corporate governance variables: the independence of the board of directors and the type of corporate governance model adopted (one-tier or two-tier), and one control variable: level of indebtedness, are relevant to explain firm’s earnings management. Results show that discretionary accruals increase with the independence of the board of directors. Moreover, companies who adopt the two-tier model are less prone to increase accruals due to a greater separation of functions and supervision and an increase in the monitorization of opportunistic behaviors. Finally, this study provides evidence that a high level of indebtedness is a deterrent to earning management practices since creditors also monitor the company’s financial situation.